2021
DOI: 10.1101/2021.06.01.446651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3-hydroxyanthranilic acid – a new metabolite for healthy lifespan extension

Abstract: The metabolism of tryptophan to nicotinamide adenine dinucleotide (NAD+) through the kynurenine pathway is increasingly linked to aging and age-associated disease. Kynurenine pathway enzymes and metabolites influence a range of molecular processes critical to healthy aging, including regulation of inflammatory and immune responses, cellular redox homeostasis, and energy production. Aberrant kynurenine metabolism is observed during normal aging and has been implicated in a range of age-associated pathologies, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The red 3HAA becomes visible under a dissection microscope by 11 days of age, or day 8 of adulthood ( Fig. 1B ) 9 . C. elegans , like mammals, experience a decline in immune function that results in increased susceptibility to pathogenic challenge with age.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The red 3HAA becomes visible under a dissection microscope by 11 days of age, or day 8 of adulthood ( Fig. 1B ) 9 . C. elegans , like mammals, experience a decline in immune function that results in increased susceptibility to pathogenic challenge with age.…”
Section: Resultsmentioning
confidence: 98%
“…C. elegans with deletion mutations in four genes— kmo-1, kynu-1, haao-1 , and umps-1 —were raised on a live gram-negative E. coli food source (strain HT115, which are mildly pathogenic to C. elegans ) 33 and challenged with the highly pathogenic gram-negative PA14 strain P. aeruginosa at the 4 th larval stage (L4). Deletion of kynu-1 and haao-1 , which encode kynureninase (KYNU) and HAAO, the enzymes are responsible for the synthesis and degradation of 3HAA, respectively and are both long lived on E. coli 9,34 and modestly resistant to PA14 challenge at L4 ( Fig. 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A ) and this metabolite modifies the redox state of the cell by modulating the redox properties of the environment. Our previous findings demonstrate that haao-1 knockdown induces an increase in 3HAA to up to 10-fold while just moderately decrease NAD+ in worms (Dang et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Oxenkrug showed that genetic (2010) or pharmacological inhibition (2013) of TDO (encoded by the vermillion gene) extended lifespan in the fruit fly Drosophila melanogaster . Knockdown of haao-1 , the gene encoding HAAO in C. elegans , or two other gene encoding kynurenine pathway enzymes, kynu-1 and tdo-2 , increases in lifespan (Dang et al, 2021; Sutphin et al, 2017; van der Goot et al, 2012). Our initial report on the benefits of haao-1 knockdown in aging suggested the importance of activating the Nrf2/SKN-1 oxidative stress response, but the specific mechanism of how this happens has not been fully elucidated (Dang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%